Effect of viscous dissipation and thermal radiation on heat transfer over a non-linearly stretching sheet through porous medium - Nandeppanavar, Mahantesh M.; Siddalingappa, M.N. (Zielona Góra: Uniwersytet Zielonogórski)
In this present paper, we have discussed the effects of viscous dissipation and thermal radiation on heat transfer over a non-linear stretching sheet through a porous medium. Usual similarity transformations are considered to convert the non-linear partial differential equation of motion and heat transfer into ODE?s. Solutions of motion and heat transfer are obtained by the Runge-Kutta integration scheme with most efficient shooting technique. The graphical results are presented to interpret various physical parameters of interest.
Keywords: porous media; viscous dissipation; Runge-Kutta method; thermal radiation; wall temperature gradient; wall temperature